2022
DOI: 10.1155/2022/9595704
|View full text |Cite
|
Sign up to set email alerts
|

The Nervous System Contributes to the Tumorigenesis and Progression of Human Digestive Tract Cancer

Abstract: Tumors of the gastrointestinal tract are one of the highest incidences of morbidity and mortality in humans. Recently, a growing number of researchers have indicated that nerve fibers and nerve signals participate in tumorigenesis. The current overarching view based on the responses to therapy revealed that tumors are partly promoted by the tumor microenvironment (TME), endogenous oncogenic factors, and complex systemic processes. Homeostasis of the neuroendocrine-immune axis (NEI axis) maintains a healthy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 108 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Eleven studies 25 , 27 - 31 , 33 , 35 - 38 reported the association between the level of nestin expression in cancer tissue and OS in patients with DTCs. Pooled results showed that higher expression of nestin (positive) in tumor was associated with worse OS (HR: 1.38, 95% CI: 1.11 to 1.72, P = .004, I 2 = 68%; Figure 2A ) in patients with DTCs. Sensitivity analyses by excluding 1 dataset at a time showed consistent results (HR: 1.30 to 1.47, P all <.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies 25 , 27 - 31 , 33 , 35 - 38 reported the association between the level of nestin expression in cancer tissue and OS in patients with DTCs. Pooled results showed that higher expression of nestin (positive) in tumor was associated with worse OS (HR: 1.38, 95% CI: 1.11 to 1.72, P = .004, I 2 = 68%; Figure 2A ) in patients with DTCs. Sensitivity analyses by excluding 1 dataset at a time showed consistent results (HR: 1.30 to 1.47, P all <.05).…”
Section: Resultsmentioning
confidence: 99%
“…Then, HRs and SEs were logarithmically transformed in order to normalize the distribution and stabilize the variance of the data. 39 The between-study heterogeneity was assessed by the Cochrane’s Q test, and the estimated I 2 statistic. 42 An I 2 >50% reflects a significant heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurexin 3 (NRXN3) encodes a protein involved in synaptic signaling and neural development in the nervous system [ 83 ]. Overlaps between genes involved in neural development and in cancer suggest links between nervous system development and tumorigenesis [ 84 , 85 ]. Emerging research suggests a role of NRXN3 in cancer progression, including breast cancer [ 86 ], through its involvement in cellular adhesion, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%